Perbandingan Protokol PPTP dan SSTP untuk Optimalisasi Jaringan VPN menggunakan metode DMVPN - Salman, Ade; Rahmatulloh, Alam (DINAMIS, 2024)
Organizations using Virtual Private Network (VPN) are essential to keep their network connections secure and efficient in the current era of digitalization. this research aims to study and compare two VPN protocols in terms of security, memory usage, and CPU speed of PPTP and SSTP protocols, considering how they improve the security and performance of applications. PPTP networks are known for being easy to use but have a lower level of security, SSTP offers flexibility in communication between nodes with strong encryption using certificates for encryption. The performance, scalability, and security of both protocols were evaluated using the DMVPN method. The results show that SSTP is more effective and secure for organizations with complex network requirements with 10% attack vulnerability accuracy, while PPTP is better for easier use with lower security levels with 70% vulnerability accuracy when used in complex networks. Both protocols can use memory resources with a 30% difference in memory usage where PPTP requires 20% of the total memory used in the client while SSTP requires 50% of the total memory in the client, this can make a reference for companies that will use VPN networks.